Археологічні матеріали з розкопок В.А. Богусевича у Чернігові в 1947—1953 рр. - Мудрицька, В.Г.; Черненко, О.Є. (Археологія, 2003)
Планомірне та систематичне вивчення стародавнього Чернігова, другого після Києва центра Подніпров’я, розгорнулося наприкінці 1940-х — на початку 1950-х років і проводилося в рамках комплексного дослідження міст Київської Русі, розпочатого в колишньому СРСР у повоєнні роки. Планомерное и систематическое изучение древностей Чернигова началось в 40—50-х гг. XX в. Одним из исследователей был В.А. Богусевич, проводивший археологические изыскания в 1947—1953 гг. В статье представлены материалы из этих раскопок, в настоящее время хранящиеся в различных организациях и музеях. Часть коллекции была передана в Государственный Эрмитаж; частично материалы поступили в фонды Института археологии НАН Украины. Остальные материалы попали в Черниговский исторический музей. В целом коллекция насчитывает около 8500 единиц. Авторские публикации материала из раскопок лишь частично освещают ее состав. Описания коллекций из архива Института археологии НАН Украины содержат лишь общие сведения. Авторами данной публикации представлены упорядоченные материалы из Черниговского исторического музея. Regular investigation of Chemigiv antiquities began in the forties and the fifties of the 20th century. One of the researchers was V.A.Bogusevich who provided archeological assessing from 1947 to 1953. The article deals with materials of these excavations which is kept in the different organizations and museums at the present time. The part of this collection was given the State Museum of Hermitage, partly materials were brought to the Archives of the Institute of Archaeology of the National Academy of Science of Ukraine (IA NASU). The other materials came to the Chernigiv Museum of History (CMH). As a whole the collection contains around 8500 articles. The publications made by author of excavations shows the collection just partly. The descriptions of collection from the Archive of IA NASU have only general information. The authors give putting in order materials from the Chemigiv Museum of History in present article.